Migration shapes senescence in a long-lived bird - Hugo Cayuela; Sébastien Roques; Antoine Arnaud; Christophe Germain; Arnaud Béchet; Jocelyn Champagnon (Proceedings of the National Academy of Sciences, 2025)
Each year, billions of animals migrate across the globe on diverse spatial and temporal scales. Migration behavior thus plays a fundamental role in the life cycle and Darwinian fitness of many organisms. While the influence of migration on early-life survival and reproduction is well documented, its effects on senescence (aging) in advanced age remain largely unexplored. Using a unique 44-y ring-resighting dataset from a long-lived, partially migratory bird species, the Greater Flamingo ( Phoenicopterus roseus ), we demonstrate that migration plays a key role in shaping age-specific trajectories of mortality and reproduction. Resident flamingos exhibit higher early-life demographic performances, with lower baseline mortality than migrants, resulting in longer adult lifespan. Residents also have a higher probability of breeding than migrants, though their breeding success is similar. However, residents seem to pay for their early-life advantages in old age, experiencing accelerated actuarial and reproductive senescence compared to migrants. Overall, our study highlights the critical impact of migration on survival and reproduction throughout life, thereby illustrating the role played by behavioral decisions in the biology of aging in long-lived vertebrates.